Optimalisasi Penyusunan Materi Pelatihan dan Pengembangan di PT. Mitra Akademi Perkasa: Axl Alexander Tunru, Denta Felli Ananda, Niken Purbasari , Maris Agung Triandewo - Tunru, Axl Alexander; Ananda, Denta Felli; Purbasari, RR. Niken; Agung Triandewo, Maris (Jurnal Abdimas Sosial, Ekonomi, dan Teknologi, 2023)
This internship report aims to explain the author's activities during the internship at PT. Mitra Akademi Perkasa (MAP Retail Academy) through the Magang Bersertifikat Kampus Merdeka (MBKM) Program organized by the Ministry of Education. This program is held to improve abilities and skills, so that they are in accordance with the needs of the world of work in the future. This report will explain about the company, the daily activities of the Author as part of the training and development team and how the work is divided. In addition to daily activities regarding the work provided, this report will explain other activities such as project that provided by PT. Mitra Akademi Perkasa.The results of the program that has been carried out for four and a half months are felt to be effective and efficient. Because in less than 5 months the author gain valuable experience and can fully contribute to the work done, especially in the field of human resources